How Do Firms Respond to Political Tensions? The Heterogeneity of the Dalai Lama Effect on Trade - Faqin Lin; Cui Hu; Andreas Fuchs (University of Heidelberg, Department of Economics, 2016)
Little is known about the firm-level dynamics behind trade responses to political tensions. This article reinvestigates variation in the travel pattern of the 14th Dalai Lama to study how political tensions affect trading decisions of Chinese importers. Using monthly trade data from China Customs covering imports of machinery and transport equipment from 173 countries over the 2000-2006 period, our empirical results show a significant reduction of imports in response to foreign government members' meetings with the Dalai Lama. In line with the idea that Chinese importers face a trade-off between bearing costs from suboptimal trade transactions and costs from not accommodating the government, this `Dalai Lama Effect' operates at the intensive margin, i.e., via a decrease in the import volume per importer. Examining differential effects across types of firm ownership, we find that the observed effect is driven by state-owned enterprises (and foreign-invested firms) and not by private companies. Moreover, while direct importers temporarily reduce their trade with Dalai Lama-receiving countries, there is some evidence that trade intermediaries even benefit. Overall, we find the effects to be much more short-lived than previously thought.
urn:nbn:de:bsz:16-heidok-223381
Keywords: F51; F14; P33; 330; international trade; political tensions; extensive margin; intensive margin; state-owned enterprises; firm ownership; trade intermediation; China; Tibet; Dalai Lama